Relationship between Malaysian University English Test (MUET) achievements and trait emotional intelligence (trait EI) among matriculation students - Thomas, Nur Sakinah; Noordin, Nooreen (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The number of matriculation candidates for Malaysian University English Test (MUET) has increased drastically, but the prestige of MUET achievements of MUET 2005-2011 has decreased drastically (Malaysian Examination Council, 2006). In Malaysia, (MUET) which is an entry test to university, was introduced to test the language proficiency in tertiary level. The Minister of Higher Education in Malaysia mentioned that most students who entered public universities have poor knowledge of English and the declining in English proficiency needs to be addressed immediately (The Star,27 Jan. 2007). The issues on the relationship between personality traits and academic achievements is becoming vital due to the claims by some researchers. An individual’s success depends on 25% of their IQ and 80% on the effectiveness of how they manage their emotions in life (Goleman, 1995). Little has been done in the scope of trait EI model personality in education especially in Malaysian university matriculation level. An individual’s personality traits are good predictors for academic performance. The research on trait EI has been scarce especially in Malaysia and there is no research done on trait EI and MUET in matriculation level. Therefore, the main purpose of this study is to determine whether there is a correlation between MUET achievements and trait (EI) among matriculation students. This study investigated the relationship between (MUET) achievements and trait Emotional Intelligence (trait EI) among 677 students from medicine, dentistry, science technology, law and syariah and accountancy courses at matriculation center, University Sains Islam Malaysia (USIM). The participants were administrated the TEIQue-SF self report questionnaire which was used to elicit information on the respondents’ trait EI which comprises Well being, Self control, Emotionality, Sociability and Global traits. Descriptive Statistics, including mean and standard deviation, were used to analyse the data. Pearson Correlation Analysis was used to analyze the correlation between MUET achievements and trait EI scores while Guilford’s (1973) Rule of Thumb was used to determine the strength of the relationship. The results showed significant correlation between MUET achievements and trait EI based on: Well being, Emotionality, Sociability, Global traits and the total EI scores. Implications of the study are discussed and suggestions are given for further research.